Design and characteristic analysis of flexible CNT film patch for potential application in ultrasonic therapy. (24th February 2023) - Feng, Yanxia; Zhang, Qilin; Li, Houyang; Qi, Qianshou; Tong, Zhenzhen; Rong, Dalun; Zhou, Zhenhuan
Abstract: Ultrasonic therapy has drawn increasing attention due to its noninvasiveness, great sensitivity and strong penetration capabilities. However, most of traditional rigid ultrasonic probes cannot achieve a solid interfacial contact with irregular nonplanar surfaces, which leads to unstable therapeutic effects and limitations of widespread use in practical applications. In this paper, a new flexible ultrasonic patch based on carbon nanotube (CNT) films is designed and fabricated to achieve a potential application in ultrasonic therapy. This patch is composed of a CNT film, a thermal protective layer and a heat sinking layer, and has the advantages of simple structure, soft, ultrathin and completely conforming to the treatment area. Theoretical and experimental studies are performed to investigate the acoustic and temperature fields before and after deformation. Effects of key design parameters of the patch on acoustic performances and temperature distributions are revealed. Numerical results indicate that the CNT film patch can produce ultrasounds over a wide frequency range and temperatures under the threshold of burn injury whether it is bent or not. Furthermore, it is also noted that the sound waves emitted from the bending patch are focused at the center of the bending patch, which demonstrates that the target treatment area can be controlled.